Role of isoxsuprine as a tocolytic agent in the management of preterm labor in Indian clinical practice - Coelho, Kiran; Gupta, Mukesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Preterm labor (PTL) is one of the prime etiological factors responsible for neonatal disease burden and fatality. Despite recent advances in neonatal care and obstetrics, the occurrence of PTL is increasing, and women who have previously experienced spontaneous PTL are more susceptible to PTL in the future. Currently, PTL is diagnosed based on regular uterine contractions, their frequency, and associated cervical changes. Antenatal corticosteroids and magnesium sulfate interventions can improve neonatal outcomes. Tocolytic medications can temporarily delay delivery to facilitate the administration of corticosteroids. Isoxsuprine is a preferred tocolytic agent because it significantly increases the average latency period, delays delivery by >48 hours, and is associated with improved perinatal outcomes. This review examines recommendations from expert gynecologists for the management of PTL in the Indian clinical setting. The experts opined that intravenous administration with Isoxsuprine provides the advantage of dose titration, thereby minimizing potential side effects. Moreover, continuation of oral isoxsuprine till 37 weeks as maintenance therapy was advised as per literature evidence and experts’ clinical experience. Furthermore, concomitant administration of nifedipine and magnesium sulfate was not recommended as this can lead to neuromuscular blockade and fatal respiratory arrest, due to the action of both molecules on the blockage of calcium channels. The experts also emphasized the significance of considering individual experiences with various treatment options and identified specific obstacles and difficulties related to the utilization of isoxsuprine as a tocolytic agent, thereby offering valuable insights into potential approaches to overcome these challenges.